Self-assembling peptides for stem cell and tissue engineering. (15th February 2016) - Tatman, Philip D.; Muhonen, Ethan G.; Wickers, Sean T.; Gee, Albert O.; Kim, Eung-Sam; Kim, Deok-Ho
Abstract : Self-assembling peptides serve as a versatile tool in stem cell and tissue engineering for advancing next-generation medical therapies. Abstract : Regenerative medicine holds great potential to address many shortcomings in current medical therapies. An emerging avenue of regenerative medicine is the use of self-assembling peptides (SAP) in conjunction with stem cells to improve the repair of damaged tissues. The specific peptide sequence, mechanical properties, and nanotopographical cues vary widely between different SAPs, many of which have been used for the regeneration of similar tissues. To evaluate the potential of SAPs to guide stem cell fate, we extensively reviewed the literature for reports of SAPs and stem cell differentiation. To portray the most accurate summary of these studies, we deliberately discuss both the successes and pitfalls, allowing us to make conclusions that span the breadth of this exciting field. We also expand on these conclusions by relating these findings to the fields of nanotopography, mechanotransduction, and the native composition of the extracellular matrix in specific tissues to identify potential directions for future research.